Predisposing factors associated with online gaming addiction : a systematic review - Nurmagandi, Boby; Hamid, Achir Yani S. (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Excessive online gaming can lead to physical health problems, including poor sleep quality, insomnia, cardiovascular diseases, as well as vision and wrist problems, while such psychosocial issues as stress, anxiety, depression, and decreasing levels of life satisfaction can also occur. This systematic review aims to determine the predisposing factors responsible for online gaming addiction to become reference in the prevention efforts. An article search was systematically conducted through ProQuest, ScienceDirect, Scopus, SAGE Publication, and EBSCOhost databases of 2015 – 2020 based on established inclusion and exclusion criteria, and 14 articles identified using PRISMA guidelines fulfilled the requirements. The review of these articles found that the biological predisposing factors in online gaming addiction consist of dysfunctional impulsivity, male gender, and appetite. The psychological aspects include history of physical and verbal abuse and bullying, lack of attention, stress, anxiety, depression, low level of self-resilience, self-esteem issues, low self-control, low self-efficacy, low life expectancy, motivation, emotional intelligence, and attention from the environment. Meanwhile, the sociocultural aspects are social support and control, length of time and devices used to play online games, types of online games, vulnerable social relations, hyperactivity, dissociation, sensation seeking, adequate daily activities, and active participation in online gaming communities. Predisposing factors can become a protective factor as well as risk factor of individuals in online gaming addiction based on the applied coping mechanisms.